Enigmatic morphological disparity in tarsometatarsi of giant penguins from the Eocene of Antarctica - Acosta Hospitaleche, Carolina Ileana Alicia (2011)
The only record of the Paleogene Antarctic Sphenisciformes comes from the Eocene La Meseta Formation (Seymour Island, Antarctic Peninsula). The analysis of tarso− metatarsi attributed to the genus Anthropornis (“giant” penguins) from the Argentine, Pol− ish and Swedish collections revealed an intriguing heterogeneity within these taxonomi− cally important elements of the skeleton. The unique hypotarsal morphology challenges the current systematics of large−bodied penguins and sheds new light on their evolution.